Differences in Patterns of Stimulant Use and Their Impact on First-Episode Psychosis Incidence: An Analysis of the EUGEI Study - Rodríguez-Toscano, Elisa; Alloza, Clara; Fraguas, David; Durán-Cutilla, Manuel; Roldán, Laura; Sánchez-Gutiérrez, Teresa; López-Montoya, Gonzalo; Parellada, Mara; Moreno, Carmen; Gayer-Anderson, Charlotte; E Jongsma, Hannah; Di Forti, Marta; et al. (Schizophrenia Bulletin, 2024)
Background: Use of illegal stimulants is associated with an increased risk of psychotic disorder. However, the impact of stimulant use on odds of first-episode psychosis (FEP) remains unclear. Here, we aimed to describe the patterns of stimulant use and examine their impact on odds of FEP. Methods: We included patients with FEP aged 18–64 years who attended psychiatric services at 17 sites across 5 European countries and Brazil, and recruited controls representative of each local population (FEP = 1130; controls = 1497). Patterns of stimulant use were described. We computed fully adjusted logistic regression models (controlling for age, sex, ethnicity, cannabis use, and education level) to estimate their association with odds of FEP. Assuming causality, we calculated the population-attributable fractions for stimulant use associated with the odds for FEP. Findings: Prevalence of lifetime and recent stimulant use in the FEP sample were 14.50% and 7.88% and in controls 10.80% and 3.8%, respectively. Recent and lifetime stimulant use was associated with increased odds of FEP compared with abstainers [fully adjusted odds ratio 1.74,95% confidence interval (CI) 1.20–2.54, P = .004 and 1.62, 95% CI 1.25–2.09, P < .001, respectively]. According to PAFs, a substantial number of FEP cases (3.35% [95% CI 1.31–4.78] for recent use and 7.61% [95% CI 3.68–10.54] for lifetime use) could have been prevented if stimulants were no longer available and the odds of FEP and PAFs for lifetime and recent stimulant use varied across countries. Interpretation: Illegal stimulant use has a significant and clinically relevant influence on FEP incidence, with varying impacts across countries.
Keywords: first episode psychosis; stimulant use; amphetamines; methamphetamine; population attributable fractions; SCOPUS